2017
DOI: 10.3892/or.2017.5626
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Reelin suppresses cell survival and mobility in non-Hodgkin lymphoma

Abstract: Reelin, a secreted glycoprotein, was recently demonstrated to be involved in the pathogenesis of cancer. However, its oncogenic activities in non-Hodgkin lymphoma (NHL) remain unclear. Therefore, we aimed to evaluate the functional role of reelin in NHL, and the underlying molecular mechanisms. In the present study, we analyzed reelin expression in lymphoma tissues and cell lines using immunohistochemistry, immunofluorescence staining, qRT-PCR and western blotting. Then, the expression of Reelin was silenced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Furthermore, Snail silencing successfully attenuated Reelin-induced cisplatin resistance, suggesting that the Snail-orchestrated EMT process may be a vital factor in Reelin-triggered chemoresistance of NSCLC cells. In line with our results, Reelin has been shown to promote mobility in non-Hodgkin lymphoma cells [ 16 ]. In addition, Reelin was also found to suppress the migration of hepatocellular carcinoma cells and mouse embryonic fibroblasts cells [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, Snail silencing successfully attenuated Reelin-induced cisplatin resistance, suggesting that the Snail-orchestrated EMT process may be a vital factor in Reelin-triggered chemoresistance of NSCLC cells. In line with our results, Reelin has been shown to promote mobility in non-Hodgkin lymphoma cells [ 16 ]. In addition, Reelin was also found to suppress the migration of hepatocellular carcinoma cells and mouse embryonic fibroblasts cells [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…Abnormal expression of Reelin promotes tumorigenesis, including the enhancement of cell proliferation, adhesion, and invasion [ 16 , 17 , 25 ]. Previous studies have suggested a correlation between Reelin and tumor chemoresistance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ad-p53 therapy resulted in a decrease in the immune suppressive chemokines CCL18 by >27-fold and CCL14 by >25-fold. CD209 (DC-SIGN), MARCO and RELN genes function in the down regulation of the immune system through IL10 and inhibitory tumor associated macrophage mechanisms respectively (22)(23)(24). CD209 is down-regulated by >20-fold, MARCO is down-regulated by >18-fold and RELN by > 17 fold.…”
Section: Gene Expression Profiles Induced By Ad-p53 Treatmentmentioning
confidence: 99%